Impact of COVID-19 on Supply Chains in Zimbabwe - Munharo Steven; Aniekan Edet Akpan; Edikan Friday Akpan; Chrispen Maradze Takudzwa; Ahmadi Attaullah; Eliseo Lucero-Prisno III Don (Journal of Public Health International, 2021)
Zimbabwe like many other sub-Saharan African states has been struggling to provide a quality health service delivery system. Nations with rampant corruption and ineffective bureaucracy made worse, the response towards the fight against COVID-19, Coronavirus Disease 2019. Despite the Zimbabwean government setting out protocols with international agencies such as WHO, World Health Organization to mount an effective response against COVID-19, the health system has been overstretched with lack of personal protective equipment, shortage of drugs and essential equipment and wanton corruption practices coupled with shortage of staff. Timely delivery of orders is still a challenge due to strict bureaucratic measures when transporting goods and the existing competition between countries. Manufacturers and donors are shifting their focus to their countries leaving the Zimbabwean health service underfunded and under-resourced. However, among the challenges experienced the country has been given a chance to revisit its priorities and strategize how best the government and organizations can move essential medical goods, utilize current trade agreements such as ACFTA, African Continental Free Trade Area and local drug manufacturers to produce essential medicines. Launching an efficient mechanism to end corrupt practices in procurement and supply as well as improve interagency cooperation and communication may help improve efforts to end COVID-19 in Zimbabwe.
Keywords: COVID-19